2002
DOI: 10.1093/gerona/57.8.m504
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Falling Among Community-Based Seniors Using Home Care Services

Abstract: Overall, distinguishing individuals into different fall status classifications is important from a clinical perspective, as it is the recurrent faller who would benefit to the greatest extent from fall prevention efforts and from the negative outcomes associated with multiple falls (i.e., mortality). One of the most significant barriers in determining risk factors for falls is the lack of consistency in the variables/tools used in the research. As such, utilizing a standardized tool, such as the MDS-HC, would … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
108
2
4

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(125 citation statements)
references
References 46 publications
11
108
2
4
Order By: Relevance
“…Since the consequences of fall accidents would include multiple risk factors affecting substantial disability, morbidity, and mortality for the elderly (Fletcher & Hirdes, 2002), many studies have investigated risk factors of homes and prevention strategies regarding falls (Steinman et al, 2009;Stevens et al, 2001). Fletcher & Hirdes (2002) reported that when seniors had more environmental hazards within their homes, they were 1.2 times more likely to experience falls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the consequences of fall accidents would include multiple risk factors affecting substantial disability, morbidity, and mortality for the elderly (Fletcher & Hirdes, 2002), many studies have investigated risk factors of homes and prevention strategies regarding falls (Steinman et al, 2009;Stevens et al, 2001). Fletcher & Hirdes (2002) reported that when seniors had more environmental hazards within their homes, they were 1.2 times more likely to experience falls.…”
Section: Discussionmentioning
confidence: 99%
“…The more environmental hazards that exist in a home, the more likely it is that elderly people will experience a fall (Fletcher & Hirdes, 2002). …”
Section: Literature Review 21 Home Hazards Accidents and Fallsmentioning
confidence: 99%
“…24,25 It is designed to be administered by trained assessors to ensure its effectiveness and accuracy. In the United States, it is one of the tools accredited by the Department of Health.…”
Section: Research Instrumentsmentioning
confidence: 99%
“…Yaşlı nüfus artışı beraberinde önemli sağlık problemlerine yol açmaktadır. Yapılan bazı çalışmalarda, 65 ve üzeri yalnız yaşayan yaşlıların %33'nün bakıma muhtaç ve ayrıca %63'nünde her yıl düştüğü belirtilmektedir [3,4]. Bu düşmeler iç doku hasarları, kemik kırılmaları ve kafa travması gibi ciddi yaralanmalara sebep olmaktadır.…”
Section: Gi̇ri̇ş (Introduction)unclassified